2016
DOI: 10.1055/s-0042-113387
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cartilage Degradation by Zingerone Involving the p38 and JNK MAPK Signaling Pathway

Abstract: Zingerone, an active compound that is present in cooked ginger, has been claimed to be a bioactive ingredient that holds the potential of preventing and/or treating diseases involving inflammation. In this study, zingerone was used to discover its properties against joint inflammation using interleukin-1-induced osteoarthritis in cartilage explant and cell culture models. Zingerone was supplemented into the cartilage explant and cell culture media at different concentrations along with the presence of interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…19 Ruangsuriya et al found that JNK and p38 MAPK phosphorylation was related to secondary OA after trauma. 9 This study also confirmed that the expression levels of JNK and p38 MAPK in the cartilage tissues of rats in the OA model group were significantly higher than those of the control group. However, after TDP-43-mMSCs were transplanted into the OA model rats, the expression levels of JNK and p38 MAPK in the cartilage tissues of rats were significantly lower than those of the model group.…”
Section: Figuresupporting
confidence: 77%
See 3 more Smart Citations
“…19 Ruangsuriya et al found that JNK and p38 MAPK phosphorylation was related to secondary OA after trauma. 9 This study also confirmed that the expression levels of JNK and p38 MAPK in the cartilage tissues of rats in the OA model group were significantly higher than those of the control group. However, after TDP-43-mMSCs were transplanted into the OA model rats, the expression levels of JNK and p38 MAPK in the cartilage tissues of rats were significantly lower than those of the model group.…”
Section: Figuresupporting
confidence: 77%
“…Bo et al confirmed that the activation of JNK and P38 MAPK could cause the calcification, hypertrophy, and apoptosis of chondrocytes in the articular cartilage of OA patients and participate in the imbalance of degradation and synthesis of chondrocytes . Ruangsuriya et al found that JNK and p38 MAPK phosphorylation was related to secondary OA after trauma . This study also confirmed that the expression levels of JNK and p38 MAPK in the cartilage tissues of rats in the OA model group were significantly higher than those of the control group.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Previous researches have shown that the JNK/c-Jun signaling pathway was activating by inflammatory factors and the inhibition of it could suppress the cartilage degradation [ 35 , 36 ]. The activation of JNK/c-Jun signaling pathway results in the expression of MMPs and then breaks chondrocytes of cartilage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%